A Study of the Hedge Funds Risk Factors - Yuan, Xiaoxuan (2009)
Hedge fund is considered to be an investment fund that always outperforms many other investments and has relatively low correlations with general conventional indices. It enables to make a profit no matter what situation is in the general market through dynamic investing strategies such as short selling. In this paper I would like to carry out a study of the returns of hedge fund indices during the period from 2002 to July 2009, so as to find out what underlying risk factors involved in such an investment tool though running a series of correlation and regression analysis of the relationships between sixteen hedge fund indices, which are classified into eight categories, and over a hundred potential risk factors. In addition to the commonly applied Index factors and Interest Rate factors, I would like to create Directional factors by dividing the indices into two directions, a positive upward direction and a negative downward direction. Furthermore, I will also construct the Trading Strategy factors through creating six option-like return series for hypothetical at-the-money, shallow out-of-the-money and deep out-of-the-money call and put options. Through running stepwise regressions, the dominate risk exposure factors will be extracted for each of the hedge fund indices so that it‘s possible to recognize the underlying risk factors for different hedge fund strategies. And the results show the risks of majority hedge funds locate in non-U.S. equity indices, such as DJ World Emerging, MSCI World ex USA, MSCI EAFE and FTSE 100 indices, and options trading in PHLX Gold/Silver, DJ Corporate Bond and DJ U.S. Select REIT Indices.